Total Quality Management in Forensic Medicine and Forensic Sciences - Aşıcıoğlu, Faruk (The Bulletin of Legal Medicine, 2000)
Total Quality Management (TQM), formerly adopted only by a few industrial establishments in Turkey, is nowadays gaining increased attention by public, health, education and local governmental institutions. TQM comprises, in addition to adaptation to standarts, management of all procedures aiming to improve product and service quality, interpersonal relationships of employees, or shortly expressed, all fields of work and work process quality. In the present study, we attempt to contribute to the application of TQM also in forensic medicine and forensic sciences as in many other fields of the contemporary life. We investigated all improvement-related efforts to constitute high quality service and product management undertaken by industrial and health institutions. We furthermore built up preliminary projects in the field of forensic medicine and forensic sciences, thus taking first steps on the journey to quality assurance systems and international standardization. Expectations to the progress in forensic medicine and forensic sciences, as brought forward by justice and also simply by citizens, necessitates together with increasing communication patients’ and consumers’ rights movements, cost factors, private insurance companies, justice reforms and technological as well as scientific progress, the adaptation of the idea of TQM.Key Words: Total quality management, Forensic medicine; Standardization, Accreditation, Leadership.
Keywords: total quality management; forensic medicine; standardization; accreditation; leadership